World Civilizations / Their History and Their Culture; Volume II - Burns Edward Mcnall; Ralph Philip L (W.W. Norton & Company, 1982)
One of the most popular and widely used texts in history, now contains more non-Western material than any other book in the field. List of Illustrations, Preface, The Age of Absolutism, The Intellectual Revolution of the Seventeenth and Eighteenth Centuries, India and the Far East and Africa During the Early Modern Era, The French and the Industrial Revolutions and Their Consequences, The West at the World's Center, The Emergence of World Civilizations, Rules of the Principal States, Preface.